MENGHADAPI QUALIFIED ASEAN BANK, INDONESIA: BEREKSPANSI ATAU BERTAHAN DI DALAM NEGERI? - Rismawati, Rismawati (Faculty of Law, Parahyangan Catholic University, 2016)
ASEAN Qualified Bank (QAB) as a criterium to be met by national (private or public) banks to enter the ASEAN open market is part of the effort to liberalize financial services and Banking Integration. Those national (private-public) banks which met the criteria shall be allowed to operate anywhere within the ASEAN countries and enjoy non-discriminative treatment. In this article the author analyze to what extent the Indonesian banks had responded to the demand made by QAB and compete at the regional level. Keywords: finance and banking services, ASEAN, AEC, QAB